Iron overload induces changes of pancreatic and duodenal divalent metal transporter 1 and prohepcidin expression in mice - Giorgi, Gisela (2014)
It is well known that the iron content of the body is tightly regulated. Iron excess induces adaptive changes that are differentially regulated in each tissue. The pancreas is particularly susceptible to iron-related disorders. We studied the expression and regulation of key iron proteins in the pancreas, duodenum and liver, using an animal model of iron overload (female CF1 mice injected i.p. with iron saccharate, colloidal iron form). Divalent metal transporter 1, prohepcidin and ferritin (pancreas, duodenum, liver) were assessed by immunohistochemistry; divalent metal transporter 1 (pancreas, duodenum) by Western blot. In the iron overloaded mice, prohepcidin expression increased in islets of Langerhans and hepatocytes, and divalent metal transporter 1 expression decreased in cells of islets and in enterocytes. In the iron overloaded mice, ferritin expression decreased in islets of Langerhans and increased in acinar cells; hemosiderin was localized in connective tissue cells. The inverse relationship between divalent metal transporter 1 and prohepcidin may indicate a negative regulation by hepcidin, and hence reduction of iron stores in islets of Langerhans. Our data showed that in iron overloaded mice model, induced by colloidal iron form, a coordinated expression of key iron proteins in the pancreas, duodenum and liver may occur. Further research will be necessary to determine the adaptive responses induced by iron in the pancreas.